The Implementation of Islamic Communication Ethics in The Social Actions of Netizens on Social Media of Twitter - A. Fikri Amiruddin Ihsani; Abdan Syakuuroo S.K (UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
The ethics of Islamic communication is a guide to acting on the basis of morality which is closely related to the Qur'an and the Hadith of the Prophet. The ethics of Islamic communication is important and interesting to study because it is a form of prevention against the negative effects of the use of social media. Based on the above context, the purpose of this study is to answer the question of how the motives of netizens social actions in the implementation of Islamic communication ethics on social media of Twitter. The theory used in this study is Max Weber's theory of social action which is divided into four categories, namely traditional rational action, instrumental rational action, effective rational action, and value oriented rational action. This study used descriptive qualitative method. The motives of netizens social actions in the implementation of Islamic communication ethics on social media of Twitter are very diverse including Qawlan Sadidan (correct words), Qawlan Baligha (effective and well targeted), Qawlan Karima (noble words), Qawlan Ma'rufan (good words) or appropriate), Qawlan Layyina (gentle), and Qawlan Maisura (easily accepted).